Hardened body

A cured geopolymer product with controlled voids and high-temperature-resistant additives addresses the need for improved fire resistance in building materials by maintaining structural integrity and suppressing melting at high temperatures.

JP2024178083APending Publication Date: 2024-12-24SEKISUI CHEMICAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023168487
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-12
Filing Date
2023-09-28
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Existing fire-resistant materials, such as those based on geopolymers, do not provide sufficient fire resistance when exposed to high temperatures, and there is a need for improved fire resistance in building materials.

Method used

A cured geopolymer product is developed with specific void ratios, high-temperature resistance, and controlled shrinkage, achieved by using certain aggregates and additives, such as wollastonite and aluminum hydroxide, to maintain voids and suppress melting.

Benefits of technology

The cured geopolymer product maintains fire resistance at high temperatures, with improved structural integrity and reduced shrinkage, enhancing its ability to withstand fire and heat exposure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024178083000001_ABST
    Figure 2024178083000001_ABST
Patent Text Reader

Abstract

To provide a hardened body having improved fire resistance.SOLUTION: A cured body is made by curing a composition for generating a geopolymer that includes a geopolymer raw material powder and an activator, wherein: (A) in a cross-sectional observation of a small test piece having a volume of 1 cm3 or more and 10 cm3 or less, the total area ratio of voids in the range of 0.022 μm2 or more and 7.065 μm2 or less is 3% or more; and (B) a total area ratio of voids in the range of 0.022 μm2 or more and 7.065 μm2 or less, as determined from a cross-sectional observation of the small test piece having a volume of 1 cm3 or more and 10 cm3 or less is 3% or more, the small test piece being prepared after being heated in an electric furnace at a rate of 10°C / min from room temperature to 800°C, held at 800°C for 60 minutes, and then cooled to room temperature.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a cured product. [Background technology]

[0002] Portland cement has traditionally been widely used as a non-flammable inorganic material, and lightweight cellular concrete, which is made from silica, cement, and quicklime as the main ingredients, with aluminum powder added as a foaming agent and cured with high-temperature, high-pressure steam in an autoclave, is well known. Taking advantage of its bubble-containing structure and non-flammable properties, lightweight cellular concrete is used as a lightweight building material, fireproof insulation material, soundproofing material, and humidity-regulating material.

[0003] However, concrete is vulnerable to acids, and it is said that its strength decreases when heated to above 500°C, so there are concerns about its use in applications where fire or acid may be involved.

[0004] Geopolymers have been attracting attention in recent years as a technology for producing concrete that does not use Portland cement. Geopolymers are hardened products made by reacting alumina-silica powder with an alkaline solution, and the aluminosilicate structure at the core of the polymer is known to be resistant to heat and acid.

[0005] Fireproof coating materials using geopolymers have also been researched. For example, Patent Document 1 describes a fireproof coating material that has a density of 1.0 g / cm3, which is obtained by adding an alkaline solution to a mixture containing an active filler, an inactive filler, a lightweight fireproof aggregate, and a foaming agent, kneading the mixture, and curing the mixture. 3 The following geopolymer-based lightweight fire-resistant material is disclosed: [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2022-117872 A Summary of the Invention [Problem to be solved by the invention]

[0007] The fire-resistant material disclosed in the above Patent Document 1 is a geopolymer-based lightweight fire-resistant material that is less likely to crack or deform when exposed to heat, but there is a demand for further improvement in fire resistance.

[0008] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide a hardened body having improved fire resistance. [Means for solving the problem]

[0009] In order to achieve the above object, the hardened body of the first disclosure is a hardened body obtained by hardening a geopolymer generating composition containing a geopolymer raw material powder and an activator, (A) The volume of the hardened body is 1 cm 3 More than 10cm 3 In the cross-sectional observation of the following small test pieces, 0.022 μm 2 More than 7.065μm 2 The total area ratio of voids in the following range is 3% or more, and (B) The volume of the hardened body is 1 cm 3 More than 10cm 3 The following small test piece is heated from room temperature to 800°C at a heating rate of 10°C / min in an electric furnace, held at 800°C for 60 minutes, and then cooled to room temperature. The cross-sectional observation of the small test piece after the heat treatment shows a 0.022μm. 2 More than 7.065μm 2 The total area ratio of voids falling within the following ranges is 3% or more.

[0010] In this way, even after the temperature is raised to 800°C, sufficient voids remain, so melting is suppressed and fire resistance can be improved. The room temperature is 23°C.

[0011] The cured body of the second disclosure is the cured body of the first disclosure, in which (C) after heat treatment, the one-dimensional shrinkage rate of a small test piece is 15% or less.

[0012] In this way, by making the one-dimensional shrinkage rate after heat treatment 15% or less, the fire resistance can be improved.

[0013] The cured body of the third disclosure is the cured body of the first or second disclosure, in which (D) the pore distribution before and after heat treatment has a maximum pore volume of 0.1 ml / g or more in the region of 0.01 μm or more and 1 μm or less.

[0014] Since sufficient voids remain even after the temperature is raised to 800° C. in this way, the fire resistance can be improved.

[0015] The hardened body of the fourth disclosure is the hardened body of the first or second disclosure, wherein the geopolymer generating composition contains aggregate, and the Ca component in the solid content excluding the aggregate is 2 wt % or less.

[0016] This results in a geopolymer generating composition that is slag-free and has a higher melting temperature, improving fire resistance.

[0017] The hardened body of the fifth disclosure is the hardened body of the first or second disclosure, wherein the geopolymer generating composition includes an aggregate having a melting point of 1000°C or higher.

[0018] By including such a highly heat-resistant aggregate, shrinkage at high temperatures can be suppressed.

[0019] The hardened body of the sixth disclosure is the hardened body of the first or second disclosure, wherein the geopolymer generating composition does not contain aggregate and the Ca component in the solid content is 2 wt% or less.

[0020] This results in a geopolymer generating composition that is slag-free and has a higher melting temperature, improving fire resistance.

[0021] The hardened body of the seventh disclosure is the hardened body of the first or second disclosure, and contains aluminum hydroxide, magnesium hydroxide, calcium aluminate, gypsum, or calcium carbonate as a heat absorbing material.

[0022] The temperature of the heat being transmitted is lowered by the latent heat, thereby improving fire resistance.

[0023] The cured product of the eighth disclosure is the cured product of the first or second disclosure, which is a foam.

[0024] By replacing a portion of the geopolymer generating composition or aggregate per volume with air, heat transfer can be reduced and fire resistance can be improved.

[0025] The cured body of the ninth disclosure is the cured body of the first disclosure, and has an expansion ratio of 1 to 6. If the expansion ratio is greater than 6, the cell structure may be destroyed due to excessive expansion, and fire resistance may deteriorate, so by setting the expansion ratio to 6 or less, heat transfer can be suppressed and fire resistance can be improved.

[0026] The hardened body of the tenth disclosure is the hardened body of the eighth disclosure, and has an expansion ratio of 1.3 to 3. This makes it possible to suppress heat transfer and improve fire resistance. Effect of the Invention

[0027] According to the present disclosure, it is possible to provide a cured body having improved fire resistance. [Brief description of the drawings]

[0028] [Figure 1] FIG. 2A is a schematic perspective view showing an example of a cured body according to an embodiment of the present disclosure, and FIG. 2B is a schematic perspective view showing a cured body with an exposed cross section. [Diagram 2] FIG. 2(a) is a SEM image of the cured body of Example 2 before heat treatment, and FIG. 2(b) is a diagram showing the state in which image analysis is performed on FIG. 2(a) to detect pores having a size of 0.022 μm2 or more and 7.065 μm2 or less. [Diagram 3] FIG. 3(a) is a SEM image of the cured body of Example 2 after heat treatment, and FIG. 3(b) is a diagram showing the state in which image analysis is performed on FIG. 3(a) to detect pores having a size of 0.022 μm2 or more and 7.065 μm2 or less. [Figure 4] 13(a) is a photograph showing the state of the cured body of Example 2 before the fire resistance was evaluated, and (b) is a photograph showing the state of the cured body of Example 2 after the fire resistance was evaluated. [Diagram 5] FIG. 5(a) is a SEM image of the cured body of Comparative Example 3 before heat treatment, and FIG. 5(b) is a diagram showing the state in which pores having sizes of 0.022 μm2 or more and 7.065 μm2 or less were detected by image analysis of FIG. 5(a). [Figure 6] FIG. 6(a) is a SEM image of the cured body of Comparative Example 3 after heat treatment, and FIG. 6(b) is a diagram showing the state in which image analysis is performed on FIG. 6(a) to detect pores having sizes of 0.022 μm2 or more and 7.065 μm2 or less. [Figure 7] 13(a) is a photograph showing the state of the cured body of Comparative Example 3 before the fire resistance was evaluated, and (b) is a photograph showing the state of the cured body of Comparative Example 3 after the fire resistance was evaluated. [Figure 8] 1 is a graph showing the relationship between the expansion ratio and fire resistance in Examples 2, 4, 5, and 6 and Comparative Example 4. [Figure 9] (a) is a photograph showing a cross section of the hardened body of Example 2. (b) is a photograph showing a cross section of the hardened body of Example 5. (c) is a photograph showing a cross section of the hardened body of Example 6. (d) is a photograph showing a cross section of the hardened body of Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] The cured product according to an embodiment of the present invention will be described below.

[0030] (hardened body) The hardened body of this embodiment is a hardened composition for generating geopolymers containing a geopolymer raw material powder and an activator. (A) The volume of the hardened body is 1 cm 3 More than 10cm 3 In the cross-sectional observation of the following small test pieces, 0.022 μm 2 More than 7.065μm 2 The total area ratio of the voids in the following range is 3% or more, and (B) the volume of the hardened body is 1 cm 3 More than 10cm 3The following small test piece is heated from room temperature to 800°C at a heating rate of 10°C / min in an electric furnace, held at 800°C for 60 minutes, and then cooled to room temperature. The cross-sectional observation of the small test piece after the heat treatment shows a 0.022μm. 2 More than 7.065μm 2 The total area ratio of voids falling within the following ranges is 3% or more.

[0031] The above-mentioned geopolymer generating composition may be used by mixing the geopolymer raw material powder and the activator and hardening them, and each component may be separated during storage and transportation. In addition, when the geopolymer generating composition contains other components described later, only a part of the composition, for example, only the geopolymer raw material powder and the aggregate, may be mixed. In this way, by storing and transporting each component separately, each component can be mixed in the amount required for construction and used as a hardened body. In addition, by storing each component without mixing, the deterioration of the properties of each component can be suppressed, so that long-term storage stability can be maintained. The components of the geopolymer generating composition can be mixed by a method commonly used in the field. The order of mixing can be set arbitrarily.

[0032] (Geopolymer raw powder) Geopolymer raw material powder is an active filler. The active filler is a powder containing glass (amorphous material) that undergoes a geopolymer-generating reaction in an alkaline environment. It is preferable that the active filler has pozzolanic activity.

[0033] A substance having pozzolanic activity is a substance that has almost no hydraulic properties by itself, but reacts with an alkali metal salt, such as calcium hydroxide, in the presence of water at room temperature to generate an insoluble compound and harden. Examples of substances having pozzolanic activity include clay, sediments, minerals, silica-based particles, coal ash, etc. Examples include clays such as metakaolin, kaolin, activated clay, and acid clay; sediments such as diatomaceous earth; minerals such as talc; silica-based particles such as silica dust, silica fume, and aerosil; and coal ash such as fly ash, white carbon, and rice husk ash.

[0034] The active filler preferably contains aluminum having an oxygen coordination number of 5. The aluminum having an oxygen coordination number of 5 is preferably contained in an amount of 10 mass% or more, preferably 20 mass% or more, based on the total aluminum contained in the active filler. Since the aluminum having an oxygen coordination number of 5 is highly reactive, it can react sufficiently with the activator at room temperature in the cured body.

[0035] In order to contain such aluminum and silicon, for example, the active filler is preferably metakaolin. The active filler preferably contains metakaolin in an amount of 30% by mass or more and 100% by mass or less, more preferably 40% by mass or more and 80% by mass or less, and even more preferably 40% by mass or more and 60% by mass or less.

[0036] Metakaolin is obtained by calcining kaolin at about 500°C to 900°C to remove some of the water of crystallization, and is amorphous and has pozzolanic activity. Metakaolin is preferably in the form of a powder. Here, powder means an aggregate of powder or particles. For example, the number average particle size (D50) of metakaolin powder is preferably 0.1 μm to 20 μm, more preferably 0.5 μm to 15 μm. Powder can be measured with a laser diffraction / scattering particle size distribution measuring device. In order to further activate metakaolin, the specific surface area of ​​the powder is set to 12 m. 2 / g or more is preferable. The specific surface area of ​​the powder means, for example, a value calculated by the BET method. The method for further activation is not limited, but methods such as pulverization classification, mechanical energy action, and thermal spraying can be used.

[0037] Any known method can be used for the pulverization and classification. For pulverization, a jet mill, a roll mill, a ball mill, etc. can be used. For classification, a sieve, specific gravity, wind force, wet sedimentation, etc. can be used. These means can be used in combination.

[0038] Methods for applying mechanical energy include those using ball media mills, media agitation mills, roller mills, etc. The applied mechanical energy is preferably 0.5 kWh / kg or more and 30 kWh / kg or less in order to minimize the load while adequately activating the material. By setting the mechanical energy in this range, the crystal structure of the raw material metakaolin can be sufficiently modified, and the reactivity of the metakaolin powder at room temperature can be improved. In addition, recrystallization of minerals such as spinel and mullite in the metakaolin powder can be suppressed, thereby maintaining or improving the reactivity at room temperature.

[0039] The thermal spraying method is a thermal spraying technique that is used for ceramic coating. Examples of the thermal spraying technique include plasma thermal spraying, high-energy gas thermal spraying, and arc thermal spraying. Preferably, the material powder is melted at a temperature of 2000°C to 16000°C, sprayed at a speed of 30 m / s to 800 m / s, and sprayed to a specific surface area of ​​12 m. 2 / g or more 100m 2 It is preferable to use a powder having a particle size of 1 / g or less.

[0040] The active filler is usually in the form of a lump or powder, but the lump or powder may be used as is. In addition, the active filler may be used after changing its state by a method such as pulverization / classification, application of mechanical energy, or thermal spraying in order to activate it. The pulverization / classification method, the application of mechanical energy, and the thermal spraying method can be the same as those described above. In particular, the material powder is melted at a temperature of 2000°C to 16000°C, sprayed at a speed of 30 m / s to 800 m / s, and sprayed to a specific surface area of ​​0.1 m. 2 / g or more 100m 2 It is preferable that the powder has a specific surface area of ​​50 μm or less. Fine particles with a large specific surface area have high reactivity and high adsorption capacity, and therefore can exhibit a stabilizing effect on metals. For example, the particle size is 50 μm or less, preferably 20 μm or less, and more preferably 5 nm to 10 μm.

[0041] The substance having pozzolanic activity preferably has an electrical conductivity difference of 0.4 mS / cm or more. From the viewpoint of reactivity with the aqueous silicate solution, the substance having pozzolanic activity more preferably has an electrical conductivity difference of 0.5 mS / cm or more, 0.6 mS / cm or more, or 0.7 mS / cm or more, and even more preferably has an electrical conductivity difference of 0.8 mS / cm or more, 1.0 mS / cm or more, or 1.2 mS / cm or more.

[0042] By achieving such an electrical conductivity difference, it is possible to ensure sufficient reactivity with the silicate aqueous solution. The electrical conductivity difference is an index related to the reactivity of a pozzolanic active substance induced by an alkaline substance, and for a substance having pozzolanic activity, the electrical conductivity of 200 ml of a saturated aqueous solution of Ca(OH)2 is measured at 40±1°C according to "Cement Concrete Research, Vol. 19, pp. 63-68, 1989", and then 5 g of metakaolin is added, stirred, and the electrical conductivity is measured two minutes later. The difference between the electrical conductivity before and after the addition is calculated, and this is taken as the electrical conductivity difference.

[0043] The active filler may contain a substance that has pozzolanic activity and an electrical conductivity difference of less than 0.4 mS / cm.

[0044] The active filler is preferably contained in an amount of 30 parts by weight or more and 150 parts by weight or less per 100 parts by weight of the activator.

[0045] It is also preferable not to use slag as the geopolymer raw material powder. This is because the melting temperature is lowered by using slag. Slag may be contained in small amounts as other components described later, but it may be contained in such a small amount that the Ca component in the solid content excluding aggregate in the hardened body is 2% by weight or less. In other words, if the hardened body does not contain aggregate, the Ca component in the solid content of the hardened body is 2% by weight or less.

[0046] (Activator) The activator includes, for example, an alkali metal. The activator includes, for example, a salt of an element belonging to Group 1, such as lithium, sodium, potassium, rubidium, cesium, or francium, and among these, the activator includes a lithium salt, a sodium salt, or a potassium salt. The activator includes, in particular, an alkali metal silicate.

[0047] The alkali metal silicate may be one or more selected from the group consisting of sodium silicate, potassium silicate, and lithium silicate. Among them, sodium silicate is preferred from the viewpoint of price and availability, and water glass is preferred. The alkali metal silicate is preferably used in the form of an aqueous solution because of its ease of handling. For example, commercially available sodium silicate, potassium silicate, lithium silicate, or a mixture thereof may be used as the alkali metal silicate. The alkali metal silicate is particularly easy to prepare using sodium silicate No. 1 to 3, sodium silicate No. 4, and sodium metasilicate No. 1 or 2 according to the JIS standard (K1408).

[0048] Alkali metal silicates such as sodium silicate, potassium silicate, and lithium silicate are generally represented by the molecular formula M2O·nSiO2, and refer to compositions and mixtures thereof in which n is in the range of 0.5 to 4.0. n is preferably in the range of 0.7 to 3.0, and more preferably in the range of 1.0 to 2.0. n can be adjusted arbitrarily by mixing the above-mentioned alkali metal silicate with an alkali metal hydroxide, such as sodium hydroxide, potassium hydroxide, or lithium hydroxide. The alkali metal hydroxide can be used in the form of either a solid or an aqueous solution.

[0049] In the geopolymer generating composition, the content of the activator is usually 10% by mass or more and 70% by mass or less, preferably 15% by mass or more and 65% by mass or less, more preferably 20% by mass or more and 60% by mass or less, and even more preferably 30% by mass or more and 55% by mass or less, based on the total mass of the geopolymer generating composition. When the content is within the above range, the mechanical strength of the hardened body obtained from the geopolymer composition tends to be improved.

[0050] When an activator, such as an alkali metal silicate, is mixed with the aforementioned geopolymer raw material powder, it induces a dehydration reaction and initiates hardening by forming Si-O bonds. As will be described later, by using a hardening accelerator, it is possible to form Si-O-metal-O-Si bonds by replacing the alkali metal of the alkali metal silicate with a divalent or higher metal, thereby accelerating hardening.

[0051] (Other Ingredients) The geopolymer generating composition may contain aggregates, heat absorbing materials, or foaming agents as components other than the geopolymer raw material powder and the activator.

[0052] The aggregate may be any one of wollastonite, perlite, SLW17, and CA6, or a mixture of at least two of these. The aggregate is contained in the hardened body in a ratio of 0 to 90% by volume relative to the total volume.

[0053] The aggregate may include needle-like or fibrous aggregate, and the above-mentioned wallasite can be used as such aggregate.

[0054] The aggregate may include lightweight aggregate. The lightweight aggregate may be, for example, the above-mentioned perlite having a grain size of 3 mm or less and a density of 0.3 g / cm. 3 The following can be used:

[0055] The aggregate preferably has a melting point of 1000°C or higher. By using aggregate with a melting point different from that of the mixture of geopolymer raw material powder and activator, it is possible to suppress the shrinkage of the hardened body due to heat.

[0056] The heat absorbing material may be any one of aluminum hydroxide, magnesium hydroxide, calcium aluminate, gypsum, and calcium carbonate, or a mixture of at least two of these materials. The heat absorbing material may be contained in the hardened body in an amount of 0 to 40% by weight based on the total weight percent.

[0057] The cured body can be made into a foam by using chemical foaming or mechanical foaming. Hydrogen peroxide or zinc stearate can be used for chemical foaming. Hydrogen peroxide is used as a foaming agent, and zinc stearate is used as a foam stabilizer. For mechanical foaming, water or an alkaline aqueous solution and a foaming agent can be used. The voids formed by the foaming agent have a diameter of 0.01 mm to 1 mm.

[0058] The expansion ratio is preferably in the range of 1 to 6. From the viewpoint of improving fire resistance, the expansion ratio is more preferably in the range of 1.6 to 3. The expansion ratio is the reciprocal of the ratio of the specific gravity of the test specimen containing gas to the specific gravity of the test specimen before containing gas using a foaming agent or a foaming agent, when the specific gravity of the test specimen before containing gas using a foaming agent or a foaming agent is set to 1.

[0059] The specific gravity of the test specimen is calculated from the weight and volume of the test specimen after it has been prepared and dried at 105°C until the mass change rate reaches 0.1%.

[0060] The expansion ratio can be calculated by (specific gravity of test specimen containing gas) / (specific gravity of test specimen before containing gas using a foaming agent or foaming agent)=(expansion ratio).

[0061] The geopolymer generating composition may further contain additives known in the art as other components. For example, hardening accelerators, fillers, modifiers, hardening retarders, surfactants, etc. These additives may be added to the geopolymer raw material powder, activator, aggregate, or a mixture thereof. As the hardening accelerator, filler, modifier, hardening retarder, surfactant, etc., known ones can be used.

[0062] The curing accelerator may be a component for accelerating the curing of the activator. The curing accelerator is preferably adjusted to a pH near neutral in order to accelerate the dehydration reaction. In addition, in order to form a Si-O-metal-O-Si bond to accelerate the curing, it is preferable to use sodium silicate, potassium silicate, or a mixture thereof that can replace the alkali metal with a divalent or higher metal. The curing accelerator preferably contains one or more compounds selected from the group consisting of organic acid esters, dialdehydes, inorganic acid esters, organic acid metal salts, inorganic acid metal salts, metal oxides, and metal hydroxides, and more preferably uses one or more compounds selected from the group consisting of organic acid esters, metal oxides, and metal hydroxides.

[0063] Organic acid esters have the advantage that they can promote the formation of Si-O bonds by generating acid in an aqueous solution. Examples of organic acid esters include carbonate esters and acetate esters. Among them, triacetin is preferred. Examples of dialdehydes include malondialdehyde. Examples of inorganic acid esters include esters of nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, etc., such as trimethyl phosphate. Examples of organic acid metal salts include alkali metal and alkaline earth metal salts of formic acid, acetic acid, malonic acid, carbonic acid, etc., such as sodium hydrogen carbonate.

[0064] Examples of inorganic acid metal salts include alkali metal salts of nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, and alkaline earth metal salts, such as magnesium sulfate. Metal oxides and metal hydroxides form Si-O-metal-O-Si bonds by dissolving metal ions, and can harden sodium silicate, potassium silicate, or a mixture thereof. Examples of metal oxides and metal hydroxides include magnesium hydroxide, magnesium carbonate, calcium carbonate, calcium hydroxide, and the like.

[0065] Examples of the filler include organic fillers (e.g., cellulose, etc.) and inorganic fillers (e.g., carbon, mineral fine powders, synthetic inorganic crystal powders, calcium carbonate, etc.) Examples of the mineral fine powders include greywacke powder, silica sand powder, zeolite, zirconia, and silica powder.

[0066] The modifier includes a substance that modifies the surface of the hardened body obtained by hardening the geopolymer generating composition to make it dense and improve the surface strength. For example, various metal salts that can react with an aqueous silicate solution are included, and light-burned magnesium oxide, zinc oxide, etc. are preferred.

[0067] Set retarders include sucrose, sodium tartrate, citric acid, metal chelating agents, and the like.

[0068] A surfactant is a substance that contributes to the dispersion stabilization of a geopolymer generating composition. The surfactant may be anionic, cationic, or nonionic. Among them, nonionic surfactants are preferred. Examples of anionic surfactants include sodium lauryl sulfate, sodium lauryl sulfate, and sodium linear alkylbenzene sulfonate. Examples of cationic surfactants include tetramethylammonium chloride, tetramethylammonium hydroxide, and monomethylamine hydrochloride. Examples of nonionic surfactants include sorbitan fatty acid esters, sucrose fatty acid esters, polyoxyethylene alkyl ethers, octaethylene glycol monododecyl ether, polyoxyethylene alkylphenyl ethers, polyoxyethylene polyoxypropylene glycol, and lauric acid diethanolamide.

[0069] These additives can be used in any amount as long as they do not impair the intended function of the hardened body. Usually, it is preferable that they are blended in an amount of 10% by mass or less based on the total mass of the geopolymer generating composition.

[0070] (State of hardened body before and after heat treatment) For a hardened body produced by mixing at least the geopolymer raw material powder and the activator, a cross section of the hardened body obtained by hardening the geopolymer generating composition is photographed at a magnification of 6000 times using a benchtop scanning electron microscope (SEM) JCM-7000 under the following photographing conditions: BED-C, incident voltage 10.0 kV, WD: 12.4. For example, a hardened body 1 as shown in Figure 1(a) is produced. The hardened body 1 has a volume of 1 cm. 3 More than 10cm 3 The small test piece is as follows. In Fig. 1(a), the shape of the hardened body 1 is cylindrical, but this is not limited to this. The upper surface of the hardened body 1 is designated as 1a, and the lower surface as 1b. This hardened body 1 is broken along the arrow A, for example with a chisel. Fig. 1(b) is a diagram showing the hardened body 1 that has been broken. The fracture surface where the flat surface is exposed from the cross section 1s of the hardened body 1 is photographed with a tabletop electron microscope.

[0071] The captured images were processed using ImageJ and AI. Based on the length of the scale bar, 1 μm is 60 pixels, so using the indicator of the circle equivalent diameter, a circle with a diameter of 1 μm is 2827 pixels, so the minimum area that can be analyzed is 1 pixel (area equivalent to a circle with a diameter of 0.16 μm = 0.022 μm 2 ) and the area range analyzed as a hole is 0.022 μm 2 More than 7.065μm 2 The total area of ​​holes with an area of ​​less than (area equivalent to a circle with a diameter of 3 μm) is calculated. The same image processing is performed before and after heating, and the area of ​​the holes with an area of ​​less than (0.022 μm 2 More than 7.065μm 2 The micropore area ratio is calculated by applying the formula: (sum of the area detected below and the area detected) / (total area of ​​the area in which the small test piece is shown in the SEM image) × 100 (%). 3 More than 10cm 3 When the micropore area ratio was calculated for the cross section of the following small test piece, the hardened body of the embodiment had a micropore area ratio of 0.022 μm 2 More than 7.065μm 2 The micropore area ratio of voids consisting of the following is 3% or more. The upper limit of the micropore area ratio is, for example, 99% or less.

[0072] In addition, the volume of the hardened body of this embodiment is 1 cm 3 More than 10cm 3 The following small test piece is heated from room temperature to 800°C at a heating rate of 10°C / min in an electric furnace, held at 800°C for 60 minutes, and then cooled to room temperature. After that, the micropore area ratio is calculated in the same manner as above. In the hardened body of this embodiment, the micropore area ratio of 0.022 μm after the heat treatment is calculated. 2 More than 7.065μm 2 The micropore area ratio of voids consisting of the following is 3% or more. The upper limit of the micropore area ratio is, for example, 99% or less.

[0073] A specific description will be given using SEM images in Example 2 described later. Fig. 2(a) is a diagram showing an SEM image of a cross section of a hardened body of Example 2 before heat treatment. Image analysis was performed on the image shown in Fig. 2(a), and it was found that the cross section was 0.022 μm.2 More than 7.065μm 2 In Fig. 2(b), image analysis was performed on Fig. 2(a) to detect pores (voids) of 0.022 μm or less. 2 More than 7.065μm 2 This is a diagram showing the state in which the following pores (voids) were detected. In FIG. 2(b), the pores are 0.022 μm 2 More than 7.065μm 2 The following pores (voids) 11 are shown filled in black.

[0074] The micropore area ratio before heat treatment can be calculated by dividing the sum of the areas of the pores 11 on the SEM image by the total area of ​​the SEM image taken in Figure 2(b) and multiplying the result by 100 (%).

[0075] Also, the hardened body 1 shown in Fig. 1(a) is heated from one side (the lower side 1b in the figure), and then broken with a chisel or the like to expose the cross section 1s shown in Fig. 1(b), and the broken surface is photographed with a tabletop electron microscope. Fig. 3(a) is a diagram showing an SEM image of the hardened body of Example 2 after heat treatment. Fig. 3(b) shows the result of image analysis of Fig. 3(a), revealing a 0.022 μm 2 More than 7.065μm 2 This is a diagram showing the state in which the following pores were detected. In FIG. 3(b), the pore size is 0.022 μm, as in FIG. 2(b). 2 More than 7.065μm 2 The following pores (voids) 11 are shown filled in black. The area ratio of micropores before heat treatment can be calculated by dividing the sum of the areas of the pores 11 on the SEM image by the total area of ​​the SEM image captured in FIG. 3(b) and multiplying the result by 100(%). In this manner, the micropore area ratio before and after the heat treatment can be calculated.

[0076] Furthermore, in the hardened body of this embodiment, the length of one side is measured using a vernier caliper before heat treatment, and the length of one side is also measured using the vernier caliper after heat treatment. The one-dimensional shrinkage ratio of the small test piece calculated from [{(length of one side before heat treatment (mm))-(length of one side after heat treatment (mm))} / (length of one side before heat treatment (mm))]×100=(one-dimensional shrinkage ratio of small test piece (%)) is 15% or less.

[0077] Furthermore, the hardened body of this embodiment is subjected to a pretreatment of drying at a constant temperature of 120°C for 4 hours using an Autobore V9620, and then the pore volume is measured in the pore diameter range of 0.0036 μm or more and 200 μm or less by mercury intrusion porosimetry, and the pore distribution is measured, which consists of the pore diameter calculated using the Washburn equation from the pore diameter measured by the above measurement method, and the maximum pore volume is 0.1 ml / g or more in the pore distribution before and after the heat treatment in the range of 0.01 μm or more and 1 μm or less.

[0078] Furthermore, when the hardened body of this embodiment is subjected to composition mapping using the above-mentioned SEM measurement method, the Ca concentration in the solid content excluding aggregate is 2% by weight or less.

[0079] The fire resistance of the hardened body of this embodiment is measured by heating a hardened body made to be 300 mm x 300 mm x 25 mm thick under conditions that produce a fire resistance curve conforming to ISO834-1, and measuring the temperature with a thermocouple at the center of the surface of a 300 mm x 300 mm x 6 mm thick steel plate made of SS400 material that is in contact with the hardened body on the non-heated side, and the time it takes for the measured temperature to reach 500°C is defined as the fire resistance.

[0080] (Example) The state of the cured body before and after the above-mentioned heat treatment will be described with reference to Examples 1 to 6 and Comparative Examples 1 to 3.

[0081] Example 1 The geopolymer generating composition of Example 1 used crushed metakaolin as the geopolymer raw material powder and water glass as the activator. The geopolymer generating composition of Example 1 contains aggregate and heat absorbing material as other components. Wollastonite and SLW17 were used as aggregate, and aluminum hydroxide was used as heat absorbing material. Water was used as diluent. The mixing amount of each material in this Example 1 and the following Examples 2 to 4 and Comparative Examples 1 to 3 is shown in Table 1 below with water glass as 100 parts by weight.

[0082] The following evaluations were carried out on the hardened bodies obtained by mixing these compositions. Hardened body 1 had the shape shown in FIG. 1(a) and a volume of 1 cm. 3 More than 10cm 3 This corresponds to the following small test piece. As described above, the hardened body 1 shown in Fig. 1(a) was broken by, for example, using a chisel, and the cross section 1s shown in Fig. 1(b) was observed using a tabletop scanning electron microscope (SEM) JCM-7000 as described above. The total area ratio was calculated as described above before the heat treatment. After the above-mentioned heat treatment, the above-mentioned total area ratio was calculated. The one-dimensional shrinkage of small test pieces of the hardened bodies after heat treatment was measured. The Ca concentration in the solid matter excluding aggregate was measured. The above-mentioned fire resistance was measured in the above-mentioned hardened form. These evaluations were performed according to the methods described above in the embodiments.

[0083] The results are shown below (Table 1).

[0084] Example 2 The geopolymer generating composition of Example 2 used crushed metakaolin as the geopolymer raw material powder and water glass as the activator. The geopolymer generating composition of Example 2 contains aggregate as another component. Wollastonite was used as the aggregate. In Example 2, compared to Example 1, only wollastonite was used as the aggregate, and no endothermic material was used.

[0085] The above evaluation was performed on the hardened body using such a geopolymer generating composition. As described above, the SEM image before the heat treatment of this Example 2 is shown in FIG. 2(a), and the result of analyzing the SEM image of FIG. 2(a) is shown in FIG. 2(b). The micropore area ratio before the heat treatment is calculated by multiplying the sum of the areas of the pores 11 shown in FIG. 2(b) by the total area of ​​the SEM image taken in FIG. 2(b) by 100(%). In addition, the SEM image after the heat treatment of this Example 2 is shown in FIG. 3(a), and the result of analyzing the SEM image of FIG. 3(a) is shown in FIG. The micropore area ratio after the heat treatment is calculated by multiplying the sum of the areas of the pores 11 shown in FIG. 3(b) by the total area of ​​the SEM image taken in FIG. 3(b) by 100(%).

[0086] In addition, Fig. 4(a) and Fig. 4(b) show the state of the hardened body of Example 2 before and after heating from the lower surface 101b in the fire resistance evaluation. Fig. 4(a) is a photograph showing the state of the hardened body before the fire resistance evaluation. Fig. 4(b) is a photograph showing the state of the hardened body after the fire resistance evaluation. Fig. 4(a) and Fig. 4(b) show that there is no change in the appearance of the hardened body before and after the fire resistance evaluation.

[0087] Example 3 The geopolymer generating composition of Example 3 used crushed metakaolin as the geopolymer raw material powder and water glass as the activator. In Example 3, compared to Example 1, no aggregate or heat absorbing material was used.

[0088] The above evaluation was carried out on the hardened body using such a geopolymer generating composition.

[0089] Example 4 The geopolymer generating composition of Example 4 used metakaolin as the geopolymer raw material powder and water glass as the activator. The geopolymer generating composition of Example 4 contains aggregate and foaming agent as other components. The aggregate was wollastonite. The foaming agent was hydrogen peroxide, and the foam stabilizer was zinc stearate. In Example 4, compared to Example 1, only wollastonite was used as aggregate, no heat absorbing material was used, and hydrogen peroxide as the foaming agent and stearic acid as the foam stabilizer were used.

[0090] The above evaluation was carried out on the hardened body using such a geopolymer generating composition.

[0091] Example 5 The geopolymer generating composition of Example 5 used metakaolin as the geopolymer raw material powder and water glass as the activator. The geopolymer generating composition of Example 5 contains aggregate and foaming agent as other components. The aggregate was wollastonite. The foaming agent was a 5% aqueous solution of pearlcrete. In Example 5, compared to Example 4, a 5% aqueous solution of pearlcrete was used as the foaming agent and no foam stabilizer was used.

[0092] The above evaluation was carried out on the hardened body using such a geopolymer generating composition.

[0093] Example 6 The geopolymer generating composition of Example 6 contains the same components as in Example 5, but the content of the 5% aqueous solution of pearlcrete is increased compared to Example 5.

[0094] The above evaluation was carried out on the hardened body using such a geopolymer generating composition.

[0095] Comparative Example 1 The geopolymer generating composition of Comparative Example 1 used crushed metakaolin and slag as geopolymer raw material powders and water glass as an activator. The above evaluation was performed on the hardened body using such a geopolymer generating composition.

[0096] Comparative Example 2 The geopolymer generating composition of Comparative Example 2 used crushed metakaolin and slag as geopolymer raw material powders and water glass as an activator. The geopolymer generating composition of Comparative Example 2 further contained perlite as an aggregate. The above evaluation was performed on the hardened body using such a geopolymer generating composition.

[0097] Comparative Example 3 The geopolymer generating composition of Comparative Example 3 used metakaolin and slag as geopolymer raw material powders and water glass as an activator. In Comparative Example 3, as shown in Table 1 below, the amount of crushed metakaolin mixed with water glass was reduced and the amount of slag mixed with water glass was increased compared to Comparative Example 1. The above evaluation was carried out on the hardened body using such a geopolymer generating composition.

[0098] Comparative Example 4 The geopolymer generating composition of Comparative Example 4 had the same components as those of Example 6, but the content of the 5% aqueous solution of pearlcrete was increased compared to Example 6.

[0099] The above evaluation was carried out on the hardened body using such a geopolymer generating composition.

[0100] Fig. 5(a) is a view showing an SEM image of the cured body of Comparative Example 3 before heat treatment. 2 More than 7.065μm 2 This is a diagram showing the results of detecting the following pores (voids). In FIG. 5(b), 2 More than 7.065μm 2 The following pores (voids) 111 are shown filled in black.

[0101] Fig. 6(a) is a view showing an SEM image of the cured body of Comparative Example 3 after heat treatment. Fig. 6(b) is a view showing the SEM image of Fig. 6(a) after heat treatment. 2 More than 7.065μm2 This is a diagram showing the results of detecting the following pores (voids). In FIG. 6(b), 2 More than 7.065μm 2 The following pores (voids) 111 are shown filled in black.

[0102] It is understood that since the hardened body of Comparative Example 3 has a low melting point, the pores decrease when heated, the void ratio decreases, and the heat resistance deteriorates.

[0103] Moreover, Fig. 7(a) is a photograph showing the state of the hardened body 101 before the fire resistance evaluation. Fig. 7(b) is a photograph showing the state of the hardened body 101 after the fire resistance evaluation. As shown in Fig. 7(b), it can be seen that cracks 101d have occurred on the upper surface 101a. This shows that the hardened body of Comparative Example 3 has inferior fire resistance to the examples.

[0104] Fig. 8 is a graph showing the relationship between the expansion ratio and fire resistance of Examples 2, 4, 5, and 6 and Comparative Example 4. Fire resistance is considered to be good when it is 80 minutes or more. The 80 minute line is indicated by M. As shown in Fig. 8, it can be seen that as the expansion ratio increases, the fire resistance improves, but if it becomes too large, it deteriorates.

[0105] FIG. 9(a) is a photograph showing a cross section of the hardened body of Example 2. FIG. 9(b) is a photograph showing a cross section of the hardened body of Example 5. FIG. 9(c) is a photograph showing a cross section of the hardened body of Example 6. FIG. 9(d) is a photograph showing a cross section of the hardened body of Comparative Example 4. All of the photographs in FIG. 9(a) to FIG. 9(d) are magnified 50 times. As shown in the figure, when the expansion ratio is 6.1 times, it can be seen that the bubbles are connected to each other. In this way, it can be seen that when the expansion is too large, the bubbles are connected to each other and the heat insulation property is deteriorated. Therefore, the expansion ratio is preferably 1 to 6 times, and more preferably 1.3 to 3 times.

[0106] (Table 1) TIFF2024178083000002.tif66155

[0107] As shown in Examples 1 to 6 and Comparative Examples 1 to 4, by not using slag as the geopolymer raw material powder, the melting point can be increased and the heat resistance can be improved. [Explanation of symbols]

[0108] 1 Hardened body 1a Top surface 1b Bottom side 1s cross section 11 Pore (void)

Claims

1. A hardened body obtained by hardening a geopolymer generating composition containing a geopolymer raw material powder and an activator, (A) Volume of the hardened body: 1 cm 3 10cm or more 3 In the cross-sectional observation of the following small test piece, 0.022 μm 2 7.065 μm or more 2 The total area ratio of voids in the following range is 3% or more, and (B) Volume of the hardened body: 1 cm 3 10cm or more 3 The following small test piece is heated from room temperature to 800°C at a heating rate of 10°C / min in an electric furnace, held at 800°C for 60 minutes, and then cooled to room temperature. The cross-sectional observation of the small test piece after the heat treatment reveals a 0.022 μm 2 7.065 μm or more 2 A hardened body having a total area ratio of voids in the following range of 3% or more.

2. (C) after the heat treatment, the one-dimensional shrinkage rate of the small test piece is 15% or less; The hardened body according to claim 1.

3. (D) The hardened body according to claim 1 or 2, wherein the pore distribution before and after the heat treatment has a maximum pore volume of 0.1 ml / g or more in the region of 0.01 μm or more and 1 μm or less.

4. The geopolymer generating composition comprises an aggregate, 3. The hardened body according to claim 1, wherein the Ca content in the solid content excluding the aggregate is 2% by weight or less.

5. The hardened body according to claim 1 or 2, wherein the geopolymer generating composition contains an aggregate having a melting point of 1000°C or higher.

6. The geopolymer generating composition does not include aggregate, 3. The hardened body according to claim 1, wherein the Ca content in the solid content is 2% by weight or less.

7. The hardened body according to claim 1 or 2, characterized in that the geopolymer generating composition contains aluminum hydroxide, magnesium hydroxide, calcium aluminate, gypsum, or calcium carbonate as a heat absorbing material.

8. The cured product according to claim 1 or 2, which is a foam.

9. The cured product according to claim 1 , having an expansion ratio of 1 to 6 times.

10. The cured product according to claim 8 , having an expansion ratio of 1.3 to 3 times.

Citation Information

Patent Citations

  • JP2022‐117872A